Resource implications of demographic change for education - McCullagh, John (Statistical and Social Inquiry Society of Ireland, 1995)
The aims of the paper are as follows: to establish how much has been spent in real terms on cere education activities at each level over the last fifteen years; to derive projections of future resource requirements of the Department of Education in the light of recent and projected demographic change; and to assess the likely implications of such change.
Read before the Society, 6 October 1994
Keywords: Educational expenditure; Future educational requirements; 314.15